Patient with basilar artery occlusion related to metastatic melanoma - Meheroz H. Rabadi, MD, MRCPI, FAAN, FANA (Radiology Case Reports, 2023)
Posterior circulation stroke accounts for approximately 20% of all ischemic strokes. The basilar artery, which is the main vessel of the posterior circulation, supplies most of the brainstem, occipital lobes and part of the cerebellum and thalami. We present a case of a 73-year-old man with known metastatic melanoma while undergoing immunotherapy presented to the emergency department with a history of progressive shortness of breath, generalize weakness, and dysphagia. The patient's imaging workup revealed brain metastasis. While hospitalized had a sudden onset of loss of consciousness which lasted a few minutes and was back to baseline. An hour later he had another episode of loss of consciousness with absence of brainstem signs. Urgent head computerized tomography showed basilar artery occlusion. Patient was transferred to the intensive care unit and started on intravenous heparin (DVT/PE dosing protocol) and supportive care. At present there is lack of high-quality evidence from randomized controlled trial to guide as how best manage patients with basilar artery occlusion.